Comparative Analysis of E-Commerce: Customer Satisfaction for Shopee and Tokopedia E-Service Quality - Ermawati Ermawati (Journal of Management and Creative Business, 2023)
This research aims to find out how the comparison of e-commerce consumer satisfaction for e-service quality of Shopee and Tokopedia in Mataram city. This type of research is descriptive comparative. The population in this study were consumers of e-commerce Shopee and Tokopedia in the city of Mataram. The data collection method used is a survey sample. The samples used in this study were 43 samples. The sampling technique uses non-probability sampling techniques with a purposive sampling approach. Data collection techniques used were questionnaires and interviews. The measurement of consumer satisfaction uses the consumer satisfaction index (CSI), and to find out whether there is a significant difference in customer satisfaction on e-service quality of Shopee and Tokopedia, a paired sample t-test is used